A Qualitative Examination of the Transition to Motherhood among Women with Histories of Childhood Trauma - Ghadaki , Maryam; Fatemi , Seyed Hossein; Frootani , Elham; Arabi , Fatemeh Sadat (Psychology of Woman Journal, 2024)
Objective: This study aims to qualitatively examine the transition to motherhood among women with histories of childhood trauma, exploring how their past experiences influence their journey into motherhood, the challenges they face, and the coping mechanisms they employ. Methods and Materials: A qualitative research design was employed, utilizing semi-structured interviews to collect data from 33 women who have experienced childhood trauma and are either pregnant or have recently become mothers. Data collection continued until theoretical saturation was reached. The interviews were transcribed verbatim, and thematic analysis was used to identify key themes and concepts within the data. Findings: Six main themes emerged from the analysis: Emotional Transition, Support Systems, Coping Mechanisms, Perceptions of Motherhood, Impact of Trauma, and Future Orientations. These themes encompassed various categories and concepts, such as anticipatory emotions, bonding experiences, partner support, self-care strategies, the impact of trauma on parenting, and aspirations for their children’s futures. The study highlights the complex interplay between childhood trauma and motherhood, underscoring the emotional challenges, the critical role of support systems, and the resilience displayed by the participants. Conclusion: The transition to motherhood for women with histories of childhood trauma is deeply affected by their past experiences, presenting unique challenges that impact their emotional well-being, parenting practices, and perceptions of motherhood. Despite these challenges, the study reveals the strength and resilience of these women, as well as the importance of targeted support and interventions to facilitate a positive transition to motherhood.